Preparation method and application of Mg-Y-Nd-Gd-Zr anode material of high-performance magnesium air battery

The magnesium alloy powder is refined through ball milling and sintering combined with extrusion deformation process, which solves the problem of limited electrical performance of the anode material of magnesium air battery, and realizes high-performance magnesium air battery anode with high discharge voltage, high energy density and high anode utilization rate. Material.

CN119410982APending Publication Date: 2025-02-11NORTHWEST INSTITUTE FOR NONFERROUS METAL RESEARCH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411597067.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The magnesium anode of magnesium air batteries has problems such as self-corrosion, slow kinetics, low actual working voltage and low anode efficiency, which limits its large-scale use.

Method used

By ball milling, the magnesium alloy powder is refined, combined with the sintering and extrusion deformation process, the grains are refined and a large number of high-active precipitation phases are generated to improve the discharge stability of the material and the anode utilization rate.

Benefits of technology

The high discharge voltage, high energy density, high power, stable discharge voltage and high anode utilization rate of magnesium air battery anode materials are achieved, and the problem of limited electrical performance of existing magnesium alloy anode materials is solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410982A_ABST
    Figure CN119410982A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a Mg-Y-Nd-Gd-Zr anode material of a high-performance magnesium air battery. The anode material is prepared from the following components in percentage by mass: 1%-9% of Y, 0.1%-4% of Nd, 0.1%-4% of Gd, 0.1%-1% of Zr and the balance of magnesium and inevitable impurities. The preparation method comprises the following steps: 1, drying magnesium alloy powder; 2, ball-milling the magnesium alloy powder; 3, spark plasma sintering; and 4, extruding and deforming. Magnesium alloy powder is refined through ball milling, grains are refined by combining sintering and extrusion deformation, a large number of high-activity precipitated phases are generated, the fine grains are beneficial to improvement of the discharge stability of the material and increase of the anode utilization rate of the material, and the high-activity precipitated phases are beneficial to improvement of the discharge voltage of the material; the material has the advantages of high discharge voltage, high energy density, high power, stable discharge voltage, high anode utilization rate and the like, and is suitable for being used as a magnesium air battery anode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chemical power source electrode materials, and specifically relates to a preparation method and application of a high-performance magnesium air battery Mg-Y-Nd-Gd-Zr anode material. Background Art

[0002] With the increase in global fossil fuel consumption and the resulting environmental pollution and other problems, the development of renewable energy and efficient energy storage systems is particularly important. Electrochemical energy storage technologies such as batteries have been widely used in power storage and transportation applications. In recent years, lithium-ion batteries have been widely used in 3C and electric vehicles due to their high energy density. However, in some emergency situations, such as maritime rescue, earthquake relief, etc., these rechargeable lithium-ion batteries may not be the most suitable. In this case, primary batteries can play a greater role because they generally have higher energy density and longer discharge time. Among them, magnesium-air batteries have attracted widespread attention due to their high theoretical voltage, large Faraday capacity, low cost and environmental friendliness. Magnesium-air batteries use metal magnesium / magnesium alloy as the anode material and oxygen in the atmosphere as the cathode reactant. When in use, adding a low concentration of aqueous electrolyte to the magnesium-air battery can activate the battery, which greatly improves the safety and standby life of the magnesium-air battery. Therefore, in addition to being used in emergency situations, magnesium-air batteries can also be used as reserve power sources in schools, hospitals and other places.

[0003] However, there are still some problems that limit the large-scale use of magnesium-air batteries, mainly including severe self-corrosion of the magnesium anode, slow kinetics, low actual working voltage, and low anode efficiency. Alloying the magnesium anode can solve some of the current problems. Common alloying elements include Al, Zn, Ca, Sn, Li, etc. In recent years, rare earth magnesium alloy anode materials have received great attention. Rare earth elements such as Nd and Gd have high active potentials, which help to increase the discharge voltage of magnesium-air batteries. However, rare earth magnesium alloy anode materials have low efficiency due to the serious "block effect". In addition, by optimizing the preparation process of rare earth magnesium alloys, their working voltage may be further improved. Therefore, it is necessary to further study the preparation process of magnesium alloys and develop magnesium-air battery anode materials with excellent discharge performance and high anode efficiency. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a method for preparing a high-performance magnesium-air battery Mg-Y-Nd-Gd-Zr anode material in view of the deficiencies of the above-mentioned prior art. The method refines the magnesium alloy powder by ball milling, and further refines the grains and produces a large number of highly active precipitated phases by combining sintering and extrusion deformation. The fine grains help to improve the discharge stability of the material and increase its anode utilization rate, while the highly active precipitated phases help to improve the discharge voltage of the material, thereby ensuring that the material has high discharge voltage, high energy density, high power, stable discharge voltage, high anode utilization and other high performance, solving the problem of limited electrical properties of magnesium alloy anode materials in the prior art.

[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a high-performance magnesium-air battery Mg-Y-Nd-Gd-Zr anode material, characterized in that the Mg-Y-Nd-Gd-Zr anode material is composed of the following components in percentage by mass: Y 1% to 9%, Nd 0.1% to 4%, Gd 0.1% to 4%, Zr 0.1% to 1%, and the rest is magnesium and unavoidable impurities; the method for preparing the Mg-Y-Nd-Gd-Zr anode material comprises the following steps:

[0006] Step 1: Drying: The magnesium alloy powder is placed in a drying oven for drying to remove trace moisture in the magnesium alloy powder;

[0007] Step 2, ball milling: ball milling the magnesium alloy powder dried in step 1 in a high-purity argon atmosphere to break the oxide layer on the surface of the magnesium alloy powder and refine the powder;

[0008] Step 3: Spark plasma sintering: The magnesium alloy powder after ball milling in step 2 is solid-state sintered by spark plasma sintering, and the surface of the sintered block is polished to remove the oxide scale to obtain a magnesium alloy billet;

[0009] Step 4: extrusion deformation: preheat the magnesium alloy billet obtained in step 3, then put it into a preheated extrusion die, and extrude it through an extruder to obtain a magnesium-air battery Mg-Y-Nd-Gd-Zr anode material.

[0010] The above-mentioned method for preparing a high-performance magnesium-air battery Mg-Y-Nd-Gd-Zr anode material is characterized in that the magnesium alloy powder in step one is spherical or quasi-spherical with a particle size of 100 mesh to 300 mesh, the drying temperature is 60°C to 100°C, and the drying time is 0.5h to 2h.

[0011] The above-mentioned method for preparing a high-performance magnesium-air battery Mg-Y-Nd-Gd-Zr anode material is characterized in that the ball-to-material ratio of the ball milling in step 2 is 5:1 to 20:1, the ball milling jar and grinding balls are made of agate or zirconia, the ball milling speed is 100rpm to 200rpm, and the time is 2h to 10h.

[0012] The above-mentioned method for preparing a high-performance magnesium-air battery Mg-Y-Nd-Gd-Zr anode material is characterized in that the process of spark plasma sintering described in step three is: the ball-milled magnesium alloy powder is loaded into a graphite or cemented carbide mold, and then transferred to a spark plasma sintering furnace for spark plasma sintering. After the sintering is completed, the vacuum is broken and the sintered block is taken out.

[0013] The above-mentioned method for preparing a high-performance magnesium-air battery Mg-Y-Nd-Gd-Zr anode material is characterized in that the sintering temperature of the spark plasma sintering in step 3 is 400°C to 480°C, the holding time is 5min to 20min, the sintering pressure is 40MPa to 60MPa, and the heating and cooling rate is 5°C / min to 30°C / min. The sintering process has a fast forming rate, a short preparation time, and the obtained magnesium alloy billet has small grains and excellent performance.

[0014] The above-mentioned method for preparing a high-performance magnesium-air battery Mg-Y-Nd-Gd-Zr anode material is characterized in that the temperature of the preheating treatment of the magnesium alloy billet in step 4 is 350°C to 500°C, the time is 0.2h to 1h, and the extrusion die is first coated with lubricating oil and then preheated at 350°C to 500°C.

[0015] The above-mentioned method for preparing a high-performance magnesium-air battery Mg-Y-Nd-Gd-Zr anode material is characterized in that the extrusion rate of the extrusion deformation in step 4 is 1 mm / s to 5 mm / s, the extrusion ratio is 10 to 40, and the magnesium alloy billet after extrusion deformation is columnar or plate-shaped, and the surface oxide scale and oil impurities of the magnesium alloy billet after extrusion deformation are removed, and then the magnesium alloy billet is cut according to the required size of the magnesium-air battery mold to obtain the magnesium-Y-Nd-Gd-Zr anode material for the magnesium-air battery.

[0016] In addition, the present invention also discloses an application of a high-performance magnesium-air battery Mg-Y-Nd-Gd-Zr anode material prepared by the above method, characterized in that the magnesium-air battery assembled from the Mg-Y-Nd-Gd-Zr anode material is used in the fields of maritime rescue and earthquake relief, and can also be used as a backup power supply or temporary power supply.

[0017] Compared with the prior art, the present invention has the following advantages:

[0018] 1. The present invention first refines the magnesium alloy powder by ball milling and removes the oxide film on the surface of the magnesium alloy powder, which helps to obtain fine grain structure through sintering. Combined with extrusion deformation of the magnesium alloy billet formed by sintering, the grains are further refined and a large number of highly active precipitated phases are generated. The fine grains help to improve the discharge stability of the material and increase its anode utilization rate, while the highly active precipitated phases help to improve the discharge voltage of the material, thereby ensuring that the material has high discharge voltage, high energy density, high power, stable discharge voltage, high anode utilization and other high performance, and is particularly suitable for use as an anode material for magnesium-air batteries.

[0019] 2. A large amount of Mg is distributed inside the Mg-Y-Nd-Gd-Zr anode material of the magnesium-air battery prepared by the present invention. 41 (Nd,Gd)5 and other second phases, which help to improve the discharge voltage and corrosion resistance of magnesium-air batteries.

[0020] 3. The present invention uses a spark plasma sintering method to carry out solid phase sintering to prepare Mg-Y-Nd-Gd-Zr anode material, which has the advantages of simple operation, short preparation time, high efficiency and dense sintered material structure, thereby simplifying the preparation process.

[0021] 4. The present invention further refines the grains of the material through hot extrusion treatment, which helps to improve the corrosion resistance of the magnesium alloy and improve the utilization rate of the Mg-Y-Nd-Gd-Zr anode material.

[0022] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is the XRD spectrum of the Mg-4.6Y-2.4Nd-1.5Gd-0.5Zr anode material prepared in Example 1 of the present invention.

[0024] Figure 2 This is a scanning electron microscope image of the Mg-4.6Y-2.4Nd-1.5Gd-0.5Zr anode material prepared in Example 1 of the present invention.

[0025] Figure 3 This is the electrochemical impedance spectrum of the Mg-4.6Y-2.4Nd-1.5Gd-0.5Zr anode material prepared in Example 1 of the present invention.

[0026] Figure 4 This is the Tafel plot of the Mg-4.6Y-2.4Nd-1.5Gd-0.5Zr anode material prepared in Example 1 of the present invention.

[0027] Figure 5The magnesium-air battery assembled with the Mg-4.6Y-2.4Nd-1.5Gd-0.5Zr anode material prepared in Example 1 of the present invention is 2 ~20mA / cm 2 Discharge performance diagram under current density.

[0028] Figure 6 This is a scanning electron microscope image of the Mg-4.6Y-2.4Nd-1.5Gd-0.5Zr anode material prepared in Comparative Example 1 of the present invention.

[0029] Figure 7 The magnesium-air battery assembled with the Mg-4.6Y-2.4Nd-1.5Gd-0.5Zr anode material prepared in Comparative Example 1 of the present invention is 2 ~20mA / cm 2 Discharge performance diagram under current density.

[0030] Figure 8 The magnesium-air battery assembled with the Mg-4.6Y-2.4Nd-1.5Gd-0.5Zr anode material prepared in Comparative Example 2 of the present invention is 2 ~20mA / cm 2 Discharge performance diagram under current density. DETAILED DESCRIPTION

[0031] Example 1

[0032] The Mg-4.6Y-2.4Nd-1.5Gd-0.5Zr anode material of the present embodiment is composed of the following components in percentage by mass: Y 4.6%, Nd 2.4%, Gd 1.5%, Zr 0.5%, and the remainder is magnesium and unavoidable impurities; the preparation method of the Mg-4.6Y-2.4Nd-1.5Gd-0.5Zr anode material comprises the following steps:

[0033] Step 1, drying: placing the spherical Mg-4.6Y-2.4Nd-1.5Gd-0.5Zr alloy powder with a particle size of 100-300 mesh in a drying oven at 60° C. for 1 hour to remove trace moisture in the Mg-4.6Y-2.4Nd-1.5Gd-0.5Zr alloy powder;

[0034] Step 2, ball milling: In a high-purity argon atmosphere with a mass purity of 99.999%, the Mg-4.6Y-2.4Nd-1.5Gd-0.5Zr alloy powder dried in step 1 is ball milled, the ball-to-material ratio of the ball milling is 15:1, the ball milling jar and the grinding balls are made of agate, the ball milling speed is 150rpm, and the time is 3h, the oxide layer on the surface of the Mg-4.6Y-2.4Nd-1.5Gd-0.5Zr alloy powder is broken and the powder is refined;

[0035] Step 3, spark plasma sintering: the ball-milled Mg-4.6Y-2.4Nd-1.5Gd-0.5Zr alloy powder is loaded into a graphite mold, and then transferred to a spark plasma sintering furnace for spark plasma sintering, and the temperature is increased to 430°C at a heating rate of 20°C / min, and kept at a sintering pressure of 50MPa for 15min. After the insulation is completed, the temperature is cooled to room temperature at a cooling rate of 20°C / min. After the sintering is completed, the vacuum is broken, the sintered block is taken out, and the surface is polished to remove the oxide scale to obtain a magnesium alloy billet;

[0036] Step 4, extrusion deformation: the magnesium alloy billet obtained in step 3 is preheated at 450°C for 0.5h, the extrusion die is first coated with lubricating oil and then preheated at 450°C, and then the preheated magnesium alloy billet is placed in the preheated extrusion die, and extruded by an extruder. The extrusion rate is 3mm / s, the extrusion ratio is 18.3, and the magnesium alloy billet after extrusion deformation is columnar. The magnesium alloy billet after extrusion deformation is cleaned to remove surface oxide scale, oil impurities, and then cut into cylinders to obtain the magnesium-air battery Mg-4.6Y-2.4Nd-1.5Gd-0.5Zr anode material.

[0037] Figure 1 is the XRD spectrum of the Mg-4.6Y-2.4Nd-1.5Gd-0.5Zr anode material prepared in this example. Figure 1 It can be seen that the Mg-4.6Y-2.4Nd-1.5Gd-0.5Zr anode material prepared by extrusion deformation mainly contains α-Mg phase and Mg 41 (Nd,Gd) 5 phases.

[0038] Figure 2 : The SEM images of the Mg-4.6Y-2.4Nd-1.5Gd-0.5Zr anode material prepared in this example, wherein Figure (a) is a SEM image along the extrusion direction, and Figure (b) is a SEM image of the cross section in the extrusion direction. Figure 2 It can be seen that the second phase in the anode material is evenly distributed along the extrusion direction, and the grain size of the anode material in the cross-sectional direction is very small, with an average grain size of about 10 μm.

[0039] Figure 3 The electrochemical impedance spectrum of the Mg-4.6Y-2.4Nd-1.5Gd-0.5Zr anode material prepared in this example is shown in Figure 2. Figure 3 Through fitting, it can be obtained that the charge transfer resistance of the anode material is about 550Ω, so the corrosion resistance of the anode material is relatively good.

[0040] Figure 4The Tafel plot of the Mg-4.6Y-2.4Nd-1.5Gd-0.5Zr anode material prepared in this embodiment is shown in FIG. Figure 4 It can be seen that the corrosion potential of the anode material is -1.545 V, and the fitted corrosion current is 90.65 μA·cm -2 .

[0041] Magnesium air battery performance test: The surface of the Mg-4.6Y-2.4Nd-1.5Gd-0.5Zr anode material prepared in this embodiment was ground and polished step by step with SiC sandpaper, and then the treated Mg-4.6Y-2.4Nd-1.5Gd-0.5Zr anode material was used as the anode, the commercial MnO2 / C composite material was used as the cathode, and the NaCl solution with a mass concentration of 3.5% was used as the electrolyte to assemble the magnesium air battery; at 1 mA / cm 2 ~20mA / cm 2 The discharge performance of magnesium-air batteries was measured at a current density of Figure 5 shown.

[0042] according to Figure 5 The test results show that the discharge voltage of the magnesium-air battery is very high, at 1mA / cm 2 , 5mA / cm 2 , 10mA / cm 2 and 20mA / cm 2 The average discharge voltages were 1.649V, 1.547V, 1.263V and 1.165V respectively when the discharge current density was 20mA / cm. At the same time, the discharge voltage of the magnesium-air battery was very stable with little fluctuation. Further calculations showed that at 20mA / cm 2 At the discharge current density, the specific energy density of the magnesium-air battery can reach 1205mWh / g, and the anode utilization rate is as high as 57.8%.

[0043] Example 2

[0044] The Mg-5.1Y-3.1Nd-0.9Gd-0.1Zr anode material of the present embodiment is composed of the following components in percentage by mass: Y 5.1%, Nd 3.1%, Gd 0.9%, Zr 0.1%, and the rest is magnesium and unavoidable impurities; the preparation method of the Mg-5.1Y-3.1Nd-0.9Gd-0.1Zr anode material comprises the following steps:

[0045] Step 1, drying: placing the spherical Mg-5.1Y-3.1Nd-0.9Gd-0.1Zr alloy powder with a particle size of 100-300 mesh in a drying oven at 100° C. for 0.5 h to remove trace moisture in the Mg-5.1Y-3.1Nd-0.9Gd-0.1Zr alloy powder;

[0046] Step 2, ball milling: In an argon atmosphere with a mass purity of 99.999%, the Mg-5.1Y-3.1Nd-0.9Gd-0.1Zr alloy powder dried in step 1 is ball milled, the ball-to-material ratio of the ball milling is 5:1, the ball milling jar and the grinding balls are made of agate, the ball milling speed is 100rpm, and the time is 10h, the oxide layer on the surface of the Mg-5.1Y-3.1Nd-0.9Gd-0.1Zr alloy powder is broken and the powder is refined;

[0047] Step 3, spark plasma sintering: the ball-milled Mg-5.1Y-3.1Nd-0.9Gd-0.1Zr alloy powder is loaded into a graphite mold, and then transferred to a spark plasma sintering furnace for spark plasma sintering, and the temperature is increased to 440°C at a heating rate of 20°C / min, and kept at a sintering pressure of 50MPa for 15min. After the insulation is completed, the temperature is cooled to room temperature at a cooling rate of 20°C / min. After the sintering is completed, the vacuum is broken, the sintered block is taken out, and the surface is polished to remove the oxide scale to obtain a magnesium alloy billet;

[0048] Step 4, extrusion deformation: the magnesium alloy billet obtained in step 3 is preheated at 470°C for 0.5h, the extrusion die is first coated with lubricating oil and then preheated at 470°C, and then the preheated magnesium alloy billet is placed in the preheated extrusion die, and extruded by an extruder. The extrusion rate is 1mm / s, the extrusion ratio is 18.3, and the magnesium alloy billet after extrusion deformation is columnar. The magnesium alloy billet after extrusion deformation is cleaned to remove surface oxide scale, oil impurities, and then cut into cylinders to obtain the magnesium-air battery Mg-5.1Y-3.1Nd-0.9Gd-0.1Zr anode material.

[0049] Example 3

[0050] The Mg-6.4Y-1.5Nd-2.7Gd-1Zr anode material of this embodiment is composed of the following components in percentage by mass: Y 6.4%, Nd 1.5%, Gd 2.7%, Zr 1%, and the rest is magnesium and unavoidable impurities; the preparation method of the Mg-6.4Y-1.5Nd-2.7Gd-1Zr anode material comprises the following steps:

[0051] Step 1, drying: placing the spherical Mg-6.4Y-1.5Nd-2.7Gd-1Zr alloy powder with a particle size of 100-300 mesh in a drying oven at 80° C. for 0.6 h to remove trace moisture in the Mg-6.4Y-1.5Nd-2.7Gd-1Zr alloy powder;

[0052] Step 2, ball milling: In an argon atmosphere with a mass purity of 99.999%, the Mg-6.4Y-1.5Nd-2.7Gd-1Zr alloy powder dried in step 1 is ball milled, the ball-to-material ratio of the ball milling is 20:1, the ball milling jar and the grinding balls are made of agate, the ball milling speed is 200rpm, and the time is 4h, the oxide layer on the surface of the Mg-6.4Y-1.5Nd-2.7Gd-1Zr alloy powder is broken and the powder is refined;

[0053] Step 3, spark plasma sintering: the ball-milled Mg-6.4Y-1.5Nd-2.7Gd-1Zr alloy powder is loaded into a graphite mold, and then transferred to a spark plasma sintering furnace for spark plasma sintering, and the temperature is increased to 440°C at a heating rate of 20°C / min, and kept at a sintering pressure of 50MPa for 20min. After the insulation is completed, the temperature is cooled to room temperature at a cooling rate of 20°C / min. After the sintering is completed, the vacuum is broken, the sintered block is taken out, and the surface is polished to remove the oxide scale to obtain a magnesium alloy billet;

[0054] Step 4, extrusion deformation: the magnesium alloy billet obtained in step 3 is preheated at 470°C for 1h, the extrusion die is first coated with lubricating oil and then preheated at 470°C, and then the preheated magnesium alloy billet is placed in the preheated extrusion die, and extruded by an extruder. The extrusion rate is 1 mm / s, the extrusion ratio is 18.3, and the magnesium alloy billet after extrusion deformation is columnar. The magnesium alloy billet after extrusion deformation is cleaned to remove surface oxide scale, oil impurities, and then cut into cylinders to obtain the magnesium-air battery Mg-6.4Y-1.5Nd-2.7Gd-1Zr anode material.

[0055] Comparative Example 1

[0056] The difference between this comparative example and Example 1 is that the extrusion deformation process in step 4 is not performed, and the magnesium alloy billet obtained in step 3 is directly used as the Mg-4.6Y-2.4Nd-1.5Gd-0.5Zr anode material for magnesium-air battery.

[0057] Figure 6 This is a scanning electron microscope image of the Mg-4.6Y-2.4Nd-1.5Gd-0.5Zr anode material prepared in this comparative example. Figure 6 It can be seen that the grain size of the Mg-4.6Y-2.4Nd-1.5Gd-0.5Zr anode material prepared without extrusion deformation is relatively large, with an average grain size of about 15 μm.

[0058] Figure 7 The magnesium-air battery assembled with the Mg-4.6Y-2.4Nd-1.5Gd-0.5Zr anode material prepared in the comparative example was 2 ~20mA / cm2 The discharge performance diagram under current density is Figure 7 and Figure 5 By comparison, it can be seen that the discharge voltage of the Mg-4.6Y-2.4Nd-1.5Gd-0.5Zr anode material prepared without extrusion deformation at different current densities is significantly lower than that of the anode material in Example 1, indicating that the extrusion deformation process can refine the grains and produce a large number of highly active precipitated phases, which helps to improve the discharge voltage of the anode material.

[0059] Comparative Example 2

[0060] The difference between this comparative example and Example 1 is that a conventional smelting method is adopted, and according to the composition of the target product magnesium air battery Mg-4.6Y-2.4Nd-1.5Gd-0.5Zr anode material, the raw material powder is weighed and placed in a crucible, which is then placed in a pit furnace under the protection of a covering agent for heating and melting, and other alloy elements are added in sequence after the magnesium raw material added first is melted, and the melt is obtained by stirring and heat preservation, and the magnesium air battery Mg-4.6Y-2.4Nd-1.5Gd-0.5Zr anode material is obtained after casting.

[0061] Figure 8 The magnesium-air battery assembled with the Mg-4.6Y-2.4Nd-1.5Gd-0.5Zr anode material prepared in this comparative example is 2 ~20mA / cm 2 The discharge performance diagram under current density is Figure 8 and Figure 7 , Figure 5 By comparison, it can be seen that the discharge voltage of the anode material at different current densities is not only significantly lower than the anode material in Example 1, but also lower than the anode material in Comparative Example 1, indicating that the present invention uses a process of ball milling, sintering combined with extrusion deformation to effectively improve the discharge voltage of the anode material.

[0062] The magnesium-air battery full cell assembled with the anode materials prepared in Examples 1 to 3 of the present invention and Comparative Examples 1 to 2 has a current density of 1 mA / cm 2 ~20mA / cm 2 The discharge performance data under the current density are shown in Table 1 below.

[0063] Table 1

[0064]

[0065]

[0066] It can be seen from Table 1 that compared with Comparative Examples 1 to 2, the magnesium-air battery assembled with the anode materials prepared in Examples 1 to 3 of the present invention has a higher conductivity than that in Comparative Examples 1 to 2. 2 ~20mA / cm2 It has high performance advantages such as high discharge voltage, high energy density, high power, stable discharge voltage and high anode utilization under current density.

[0067] Example 4

[0068] The Mg-9Y-4Nd-0.1Gd-0.4Zr anode material of the present embodiment is composed of the following components in percentage by mass: Y9%, Nd 4%, Gd 0.1%, Zr 0.4%, and the rest is magnesium and unavoidable impurities; the preparation method of the Mg-9Y-4Nd-0.1Gd-0.4Zr anode material comprises the following steps:

[0069] Step 1, drying: placing the spherical Mg-9Y-4Nd-0.1Gd-0.4Zr alloy powder with a particle size of 100-300 mesh in a drying oven at 60° C. for 2 hours to remove trace moisture in the Mg-9Y-4Nd-0.1Gd-0.4Zr alloy powder;

[0070] Step 2, ball milling: In an argon atmosphere with a mass purity of 99.999%, the Mg-9Y-4Nd-0.1Gd-0.4Zr alloy powder dried in step 1 is ball milled, the ball-to-material ratio of the ball milling is 20:1, the ball milling jar and the grinding ball are made of zirconium oxide, the ball milling speed is 200rpm, and the time is 2h, the oxide layer on the surface of the Mg-9Y-4Nd-0.1Gd-0.4Zr alloy powder is broken and the powder is refined;

[0071] Step 3, spark plasma sintering: the ball-milled Mg-9Y-4Nd-0.1Gd-0.4Zr alloy powder is loaded into a cemented carbide mold, and then transferred to a spark plasma sintering furnace for spark plasma sintering, and the temperature is increased to 480°C at a heating rate of 5°C / min, and kept at a sintering pressure of 60MPa for 20min. After the insulation is completed, the temperature is cooled to room temperature at a cooling rate of 5°C / min. After the sintering is completed, the vacuum is broken, the sintered block is taken out, and the surface is polished to remove the oxide scale to obtain a magnesium alloy billet;

[0072] Step 4, extrusion deformation: the magnesium alloy billet obtained in step 3 is preheated at 500°C for 0.5h, the extrusion die is first coated with lubricating oil and then preheated at 500°C, and then the preheated magnesium alloy billet is placed in the preheated extrusion die, and extruded by an extruder. The extrusion rate is 1mm / s, the extrusion ratio is 10, and the magnesium alloy billet after extrusion deformation is columnar. The magnesium alloy billet after extrusion deformation is cleaned to remove surface oxide scale, oil impurities, and then cut into cylinders to obtain the magnesium-air battery Mg-9Y-4Nd-0.1Gd-0.4Zr anode material.

[0073] Example 5

[0074] The Mg-4.1Y-0.1Nd-4Gd-0.5Zr anode material of this embodiment is composed of the following components in percentage by mass: Y 4.1%, Nd 0.1%, Gd 4%, Zr 0.5%, and the rest is magnesium and unavoidable impurities; the preparation method of the Mg-4.1Y-0.1Nd-4Gd-0.5Zr anode material comprises the following steps:

[0075] Step 1, drying: placing the spherical Mg-4.1Y-0.1Nd-4Gd-0.5Zr alloy powder with a particle size of 100-300 mesh in a drying oven at 80° C. for 0.5 h to remove trace moisture in the Mg-4.1Y-0.1Nd-4Gd-0.5Zr alloy powder;

[0076] Step 2, ball milling: In an argon atmosphere with a mass purity of 99.999%, the Mg-4.1Y-0.1Nd-4Gd-0.5Zr alloy powder dried in step 1 is ball milled, the ball-to-material ratio of the ball milling is 10:1, the ball milling jar and the grinding balls are made of agate, the ball milling speed is 100 rpm, the time is 2 hours, the oxide layer on the surface of the Mg-4.1Y-0.1Nd-4Gd-0.5Zr alloy powder is broken and the powder is refined;

[0077] Step 3, spark plasma sintering: the ball-milled Mg-4.1Y-0.1Nd-4Gd-0.5Zr alloy powder is loaded into a graphite mold, and then transferred to a spark plasma sintering furnace for spark plasma sintering, and the temperature is increased to 440°C at a heating rate of 10°C / min, and kept at a sintering pressure of 50MPa for 20min. After the insulation is completed, the temperature is cooled to room temperature at a cooling rate of 10°C / min. After the sintering is completed, the vacuum is broken, the sintered block is taken out, and the surface is polished to remove the oxide scale to obtain a magnesium alloy billet;

[0078] Step 4, extrusion deformation: the magnesium alloy billet obtained in step 3 is preheated at 450°C for 0.2h, the extrusion die is first coated with lubricating oil and then preheated at 450°C, and then the preheated magnesium alloy billet is placed in the preheated extrusion die, and extruded by an extruder. The extrusion rate is 3mm / s, the extrusion ratio is 25, and the magnesium alloy billet after extrusion deformation is plate-shaped. The magnesium alloy billet after extrusion deformation is cleaned to remove surface oxide scale, oil impurities, and then cut into cylinders to obtain magnesium-air battery Mg-4.1Y-0.1Nd-4Gd-0.5Zr anode material.

[0079] Example 6

[0080] The Mg-1Y-1.5Nd-1Gd-0.2Zr anode material of this embodiment is composed of the following components in percentage by mass: Y1%, Nd 1.5%, Gd 1%, Zr 0.2%, and the rest is magnesium and unavoidable impurities; the preparation method of the Mg-1Y-1.5Nd-1Gd-0.2Zr anode material comprises the following steps:

[0081] Step 1, drying: placing the spherical Mg-1Y-1.5Nd-1Gd-0.2Zr alloy powder with a particle size of 100-300 mesh in a drying oven at 70° C. for 1 hour to remove trace moisture in the Mg-1Y-1.5Nd-1Gd-0.2Zr alloy powder;

[0082] Step 2, ball milling: In an argon atmosphere with a mass purity of 99.999%, the Mg-1Y-1.5Nd-1Gd-0.2Zr alloy powder dried in step 1 is ball milled, the ball-to-material ratio of the ball milling is 15:1, the ball milling jar and the grinding balls are made of agate, the ball milling speed is 150rpm, and the time is 2h, the oxide layer on the surface of the Mg-1Y-1.5Nd-1Gd-0.2Zr alloy powder is broken and the powder is refined;

[0083] Step 3, spark plasma sintering: the ball-milled Mg-1Y-1.5Nd-1Gd-0.2Zr alloy powder is loaded into a graphite mold, and then transferred to a spark plasma sintering furnace for spark plasma sintering, and the temperature is increased to 400°C at a heating rate of 30°C / min, and kept at a sintering pressure of 40MPa for 5 minutes. After the insulation is completed, the temperature is cooled to room temperature at a cooling rate of 30°C / min. After the sintering is completed, the vacuum is broken, the sintered block is taken out, and the surface is polished to remove the oxide scale to obtain a magnesium alloy billet;

[0084] Step 4, extrusion deformation: the magnesium alloy billet obtained in step 3 is preheated at 350°C for 1h, the extrusion die is first coated with lubricating oil and then preheated at 350°C, and then the preheated magnesium alloy billet is placed in the preheated extrusion die, and extruded by an extruder. The extrusion rate is 5mm / s, the extrusion ratio is 40, and the magnesium alloy billet after extrusion deformation is columnar. The magnesium alloy billet after extrusion deformation is cleaned to remove surface oxide scale, oil impurities, and then cut into cylinders to obtain the magnesium-air battery Mg-1Y-1.5Nd-1Gd-0.2Zr anode material.

[0085] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a high-performance magnesium-air battery Mg-Y-Nd-Gd-Zr anode material, characterized in that: The Mg-Y-Nd-Gd-Zr anode material is composed of the following components in percentage by mass: Y 1% to 9%, Nd 0.1% to 4%, Gd 0.1% to 4%, Zr 0.1% to 1%, and the rest is magnesium and unavoidable impurities; the preparation method of the Mg-Y-Nd-Gd-Zr anode material comprises the following steps: Step 1: Drying: The magnesium alloy powder is placed in a drying oven for drying to remove trace moisture in the magnesium alloy powder; Step 2, ball milling: ball milling the magnesium alloy powder dried in step 1 in a high-purity argon atmosphere to break the oxide layer on the surface of the magnesium alloy powder and refine the powder; Step 3: Spark plasma sintering: The magnesium alloy powder after ball milling in step 2 is solid-state sintered by spark plasma sintering, and the surface of the sintered block is polished to remove the oxide scale to obtain a magnesium alloy billet; Step 4: extrusion deformation: preheat the magnesium alloy billet obtained in step 3, then put it into a preheated extrusion die, and extrude it through an extruder to obtain a magnesium-air battery Mg-Y-Nd-Gd-Zr anode material.

2. The method for preparing a high-performance magnesium-air battery Mg-Y-Nd-Gd-Zr anode material according to claim 1, characterized in that: In step 1, the magnesium alloy powder is spherical or quasi-spherical with a particle size of 100-300 meshes, the drying temperature is 60° C.-100° C., and the drying time is 0.5 h-2 h.

3. The method for preparing a high-performance magnesium-air battery Mg-Y-Nd-Gd-Zr anode material according to claim 1, characterized in that: The ball-to-material ratio of the ball mill in step 2 is 5:1 to 20:1, the ball mill jar and the grinding balls are made of agate or zirconia, the ball mill speed is 100 rpm to 200 rpm, and the time is 2 h to 10 h.

4. The method for preparing a high-performance magnesium-air battery Mg-Y-Nd-Gd-Zr anode material according to claim 1, characterized in that: The process of spark plasma sintering in step three is: the ball-milled magnesium alloy powder is loaded into a graphite or cemented carbide mold, and then transferred to a spark plasma sintering furnace for spark plasma sintering. After the sintering is completed, the vacuum is broken and the sintered block is taken out.

5. The method for preparing a high-performance magnesium-air battery Mg-Y-Nd-Gd-Zr anode material according to claim 1, characterized in that: The sintering temperature of the spark plasma sintering in step 3 is 400° C. to 480° C., the holding time is 5 min to 20 min, the sintering pressure is 40 MPa to 60 MPa, and the heating and cooling rate is 5° C. / min to 30° C. / min.

6. The method for preparing a high-performance magnesium-air battery Mg-Y-Nd-Gd-Zr anode material according to claim 1, characterized in that: In step 4, the magnesium alloy billet is preheated at a temperature of 350°C to 500°C for a time of 0.2h to 1h. The extrusion die is firstly coated with lubricating oil and then preheated at 350°C to 500°C.

7. The method for preparing a high-performance magnesium-air battery Mg-Y-Nd-Gd-Zr anode material according to claim 1, characterized in that: The extrusion rate of the extrusion deformation in step 4 is 1 mm / s to 5 mm / s, the extrusion ratio is 10 to 40, and the magnesium alloy billet after extrusion deformation is columnar or plate-shaped. The surface oxide scale and oil impurities of the magnesium alloy billet after extrusion deformation are removed, and then the billet is cut according to the required size of the magnesium air battery mold to obtain the magnesium air battery Mg-Y-Nd-Gd-Zr anode material.

8. An application of a high-performance magnesium-air battery Mg-Y-Nd-Gd-Zr anode material prepared by the method according to any one of claims 1 to 7, characterized in that: The magnesium-air battery assembled with the Mg-Y-Nd-Gd-Zr anode material is used in the fields of maritime rescue and earthquake relief, and can also be used as a backup power source or temporary power source.